Turn on thread page Beta
 You are Here: Home >< Maths

# Tricky Maths C3 Qquestion watch

1. tth
2. Umm...?

1. Although I suppose you could call a variable fetar, I think you're on about theta.
2. What you've given isn't an equation, have you missed out an equality sign?
3. Dude youve missed out the what your trying to proove? And why does every insist on using same symbols just say 'x' instead of theta.
4. heyyy
im sorry, clumsy mistake

prove that : cot x cosec x / sec^2 x + cosec ^2 x = cos ^3 x

thank you
5. (Original post by ash213)
heyyy
im sorry, clumsy mistake

prove that : cot x cosec x / sec^2 x + cosec ^2 x = cos ^3 x
cot x cosec x / sec^2 x + cosec ^2 x = cos ^3 x
(1/tanx.1/sinx) / (1/cos²x + 1/sin²x) = cos³x
(cosx/sinx.1/sinx) / (1/cos²x + 1/sin²x) = cos³x
(cosx/sin²x) / ((sin²x + cos²x)/cos²xsin²x) = cos³x
(cosx/sin²x) / (1/cos²xsin²x) = cos³x
(cosx/sin²x).(cos²xsin²x) = cos³x
(cos³xsin²x)/sin²x = cos³x

the sine's cancel to leave...

cos³x = cos³x
6. Damn Dekota that is fast.
7. (Original post by Dekota)
cot x cosec x / sec^2 x + cosec ^2 x = cos ^3 x
(1/tanx.1/sinx) / (1/cos²x + 1/sin²x) = cos³x
(cosx/sinx.1/sinx) / (1/cos²x + 1/sin²x) = cos³x
(cosx/sin²x) / ((sin²x + cos²x)/cos²xsin²x) = cos³x
(cosx/sin²x) / (1/cos²xsin²x) = cos³x
(cosx/sin²x).(cos²xsin²x) = cos³x
(cos³xsin²x)/sin²x = cos³x

the sine's cancel to leave...

cos³x = cos³x
When you are proving something you cannot just equate them. Start with LHS = whatever. Then simplify "whatever" until it is the RHS.
8. (Original post by samd)
When you are proving something you cannot just equate them. Start with LHS = whatever. Then simplify "whatever" until it is the RHS.
Err .. isn't this what I've done?
9. (Original post by Dekota)
cot x cosec x / sec^2 x + cosec ^2 x = cos ^3 x
(1/tanx.1/sinx) / (1/cos²x + 1/sin²x) = cos³x
(cosx/sinx.1/sinx) / (1/cos²x + 1/sin²x) = cos³x
(cosx/sin²x) / ((sin²x + cos²x)/cos²xsin²x) = cos³x
(cosx/sin²x) / (1/cos²xsin²x) = cos³x
(cosx/sin²x).(cos²xsin²x) = cos³x
(cos³xsin²x)/sin²x = cos³x

the sine's cancel to leave...

cos³x = cos³x
i agree with samd. You can't just let the expression equal the one you're trying to prove. It defeats the principle of proving it in the first place!
You must express the expression in terms of sinx and cosx and simplify until you get the required expression. Then you can say LHS = RHS.
10. Fair enough; dear pedantic mathmos.
11. I love the instant change to patronising talk - the italics and 'dear' -

Anyway, a slightly quicker way, (express everything in terms of coses and sines)

(cos x/sin x)(1/sin x)
=--------------
(1/cos^2 x) + (1/sin^2 x)

cos x
=--------------
(sin^2 x)((1/cos^2 x) + (1/sin^2 x))

cos x
=--------------
tan^2 + 1

cos x
=--------------
sec^2 x

= cos^3 x.

LHS=RHS

Turn on thread page Beta
TSR Support Team

We have a brilliant team of more than 60 Support Team members looking after discussions on The Student Room, helping to make it a fun, safe and useful place to hang out.

This forum is supported by:
Updated: November 13, 2005
Today on TSR

### Which business legend are you?

We have the answer...

### University open days

• University of Bradford
Wed, 21 Nov '18
• Buckinghamshire New University
Wed, 21 Nov '18
• Heriot-Watt University
Wed, 21 Nov '18
Poll
Useful resources

## Make your revision easier

### Maths Forum posting guidelines

Not sure where to post? Read the updated guidelines here

### How to use LaTex

Writing equations the easy way

### Study habits of A* students

Top tips from students who have already aced their exams

Can you help? Study help unanswered threads

## Groups associated with this forum:

View associated groups

The Student Room, Get Revising and Marked by Teachers are trading names of The Student Room Group Ltd.

Register Number: 04666380 (England and Wales), VAT No. 806 8067 22 Registered Office: International House, Queens Road, Brighton, BN1 3XE